The clinicopathological evaluation of 24 hours upon challenge of Streptococcus iniae in red hybrid tilapia (Oreochromis sp.) - Mazlan, Muhammad Aqmal Hakim (2016)
This study was aimed to describe the severity and immunolocalisation of the antigen of lesions in the brain, eyes and kidney in every 6 hours for 24 hours by presence or absence of stress factors before infection. Fifteen Red hybrid tilapia in duplicates were inoculated intraperitoneally with 109 CFU/mL diluted in PBS while another set, was kept for negative control. Clinical signs were recorded and observed, and samples from gills, brain, eyes and kidney were collected. Each of the samples was subjected to bacterial culture and isolation and histopathology. Immunohistochemistry (IHC) and polymerase chain reaction (PCR) were also done to detect the presence of the antigen. However, there were no obvious signs, and no macroscopic finding can be observed throughout 24 hours post challenge (hpc) of the disease. IHC were detected as early as PCR and isolation with intense staining in a blood vessel, lumen and wall, macrophages in the choroid, focal haemorrhages in the renal interstitium and meninges especially in heat stressed followed by no stressors. The immunolocalisation of the antigen is explained in the pathogenesis of streptococcosis in red tilapia. In conclusion, fish that is stressed are more likely to develop diseases and showing more severe signs of disease compared to fish that was not subjected to stress.